Kakuriyo : bed & breakfast for spirits. 2 - Yuma, Midori; Yuma, Midori; Kimura, Tomo (Shojo beat manga., 2019)
"Aoi Tsubaki inherited her grandfather's ability to see spirits--and his massive debt to them! Now she's been kidnapped and taken to Kakuriyo, the spirit world, to make good on his bill. Her options: marry the head of the inn her grandfather trashed, or get eaten by ayakashi. But Aoi isn't the type to let spirits push her around, and she's determined to redeem her grandfather's IOU on her own terms! ... Aoi's having no luck finding a job at the Tejin-ya inn, but a chance encounter with the tengu Matsuba might give her another option! Her home cooking and kind manner impress the crow demon, and when he finds out why she's in Kakuriyo, he offers to welcome her into his family as a daughter-in-law to pay off her debt! Can the still unemployed Aoi afford to turn down such a generous offer?"--Page [4] of cover.